Efficient Management of Aircraft Taxiing Phase by Adjusting Speed Through Conflict-Free Routes - Idrissi, Otmane; Bikir , Abdelmounaime; Mansouri , Khalifa (Statistics, Optimization & Information Computing, 2022)
Air traffific congestion is considered to be the main problem in air traffific management. It represents a real handicap in the current rising air traffific flflows without a corresponding enhancement in airport infrastructure. This issue leads to more workloads for air traffific controllers, air stakeholders and other airport operations. The following paper aims to minimize the departure aircraft taxiing time in the movement area. This duration can be affected by several factors such as routing, taxiing speed, holding while taxiing ... etc. In this work, we are going to solve the previous problem by using a tactical planning tool: it consists on assigning effificient and nonstop routes to the scheduled traffific on departure. This tool, using a real-time algorithm, will detect in advance routing conflflicts and solve them before aircraft leave stands and approach the hotspots in taxing network. Furthermore, the proposed method will optimize the use of the available ground network by acting on the taxiing speed in order to reduce departures’ delays, fuel consumption and gas emissions.